Film, Medicine and Freemasonry: Jenő Janovics and the Transylvanian “Hollywood”: The Freemasonry of Cluj – the perfect connection between medicine and society - Varga, Attila (DELTOS, 2024)
This study highlights the life and work of Jenő Janovics, a renowned Hungarian theater director in Cluj, the capital of Transylvania. Janovics was a multi-talented figure, excelling as a film director and actor, and was also a freemason. Often hailed as the creator of Transylvanian “Hollywood”, he directed a total of 66 films. One of them, “The Horror of the World” (Hu: “Világrém”, 1920), focuses on medicine and its preventive role in safeguarding societal health. Using cinematography, Janovics expressed the concerns of both the physicians and the freemasons of Cluj regarding the detrimental impact of immorality and veneral diseases on the individual and the nation. At a time of profound political, territorial and social changes, this silent movie highlights the importance of medicine in society.